2014
DOI: 10.1111/tbj.12340
|View full text |Cite
|
Sign up to set email alerts
|

Fibromatosis Associated with Silicone Breast Implant: Ultrasonography and MR Imaging Findings

Abstract: Desmoid type fibromatosis is an uncommon benign disease entity of which its etiology is currently unknown. It constitutes 0.3% of all solid neoplasms, but it is rarely seen in the breast and even more scarcely reported to develop in association with breast implant. We present ultrasonography and magnetic resonance imaging findings of a 29-year-old female patient with fibromatosis after breast implant surgery. Knowledge of imaging findings of breast fibromatosis associated with implant will be helpful for accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…In all 10 of these cases, the tumor had a well-defined border. Prior studies have reported implant-associated fibromatosis as having a smooth margin on both CT and MRI with a band-like hypointense portion on MRI [13] , [33] . However, our imaging findings are different from those previously reported.…”
Section: Discussionmentioning
confidence: 95%
“…In all 10 of these cases, the tumor had a well-defined border. Prior studies have reported implant-associated fibromatosis as having a smooth margin on both CT and MRI with a band-like hypointense portion on MRI [13] , [33] . However, our imaging findings are different from those previously reported.…”
Section: Discussionmentioning
confidence: 95%
“…Most of them occur sporadically;5 however, intra-abdominal desmoid tumors seem to be related to FAP or GS and any germ line mutation 13. A prior history of trauma has been reported to be associated with this tumor in one of every four patients14 and has also been associated with fibromatosis of the breast and breast augmentation 2,5,12,15,16. Fibromatosis of the breast can occur primarily due to breast parenchyma and by secondary invasion from the musculoaponeurotic layer of the pectoral muscle.…”
Section: Discussionmentioning
confidence: 99%
“…This is a comparable percentage with that stated in literature [1,10] It was best traced in the post-contrast images. The literature highlighted its importance, not just as distinguishing feature of deep fibromatosis but more importantly as a guide for excision with free surgical margins [16,17] Qualitative analysis of the DWIs and the ADC map showed the predominance (92.5% of lesions) of high signal intensity on the DWIs, whether purely or mixed with low signal areas. On the corresponding ADC map, this was reflected as intermediate or mixed intermediate and low signal intensity, reflecting diffusion restriction.…”
Section: Discussionmentioning
confidence: 99%